Freedom privation under framework of human rights - Murillo Leiva, William José (2018)
The present essay intends to analyze the conditions of imprisonment in relation to Human Rights and some aspects about these conditions in which violations of these rights are often visualized.  Thus, it reflects on the prison space as a place that attempts against respect for life and human dignity. Finally, discuss on some of the considerations that a government must bear in mind to achieve an effective respect for the Human Rights of persons deprived of freedom.